Über klimatische Trockentäler im Himalaya - Schweinfurth, Ulrich (ERDKUNDE, 1956)
Climatically dry valleys can be found everywhere in the Himalayas. This is not surprising in the northwestern section where the mountains rise out of the dry belt which stretches from the Middle East to Central Asia. The occurrence of climatically dry valleys is, however, astonishing in the eastern part of the Himalayas in areas where the climate in its general character is humid. There we frequently find a dry or very dry valley bottom which gradually or even more often abruptly gives rise on the valley sides to damp or very damp forests. Observations of this phenomenon in the great river gorges in the east (by Ward, Schäfer, Rock), from Bhutan (by Griffith, Ludlow), and from Nepal (by Williams, Polunin) correspond very closely to those made by Troll in the Bolivian Andes. From his experience in South America Troll pointed to this phenomenon as a characteristic feature of tropical mountain regions. An explanation of the dry valley bottoms which occur simultaneously with cloud banks on both slopes at a certain height, and their connexion with a diurnal range of winds is difficult.